The Effectiveness of The Use of Simple Teaching Aids on The Learning Motivation of Class X Students of SMK Kristen Harapan Rantepao on Business And Energy Materials - Rante Payung, Adel; Lolang, Enos; Saka, Bergita Gela SukuMu; Pakiding, Alexander; Silka, Silka (Jurnal Literasiologi, 2024)
The purpose of this study is to determine the effectiveness of the use of simple teaching aids on the learning motivation of grade X students of SMK Harapan Kristen Rantepao. In this study, the method used was an experimental method with a quasi-experimental research design of a nonequivalent control group design. The sample in this study is students of class X Tab B and X Tab H of SMK Harapan Kristen Rantepao. The instruments used in this study are test and questionnaire instruments. Data analysis technique using SPSS 21.The results of the study showed that the use of teaching aids as a learning medium could increase the motivation to learn physics of grade X students of Harapan Rantepao Christian Vocational School on business and energy materials. This can be seen in the experimental class from an increase in the average pretest result of 28.36 to 81.00 in the posttest. In the control class, the average increase in pretest test results of 27.73 increased to 76.36 in the posttest. Meanwhile, in the t-test, the sig value (2-tailed) was 0.005 < 0.05. These results show that there is a difference in student learning outcomes between the experimental class and the control class.